ANALYSIS OF MOTOR SPHERE OF CHILDREN OF EARLY AGE DIAGNOSED WITH AUTISM SPECTRUM DISORDERS - Tomilova, S.V.; Kostyuk, A.V.; Mashtakova, A.M.; Tenkacheva, T.R. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the specifics of the motor sphere of children of early age diagnosed with autism spectrum disorders. Methods and structure of the study. The study of the motor functions of children of early age diagnosed with autism spectrum disorders was carried out at the "Logoped" Center (Pervouralsk, Sverdlovsk Region) and the Center for Continuing Education of the Ural State Pedagogical University (Yekaterinburg) from 2018 through 2021. Sampled for the study were 9 children aged from 1 year 3 months to 2 years 8 months, all diagnosed with autism spectrum disorders by a child psychiatrist. The study was conducted prior to the start of the behavioral intervention. The subjects’ motor functions were analyzed using a program for assessing the level of motor development at early childhood (Peabody Developmental Motor Scales), including six subtests, which was supplemented by the corresponding sections from the Assessment of Basic Language and Learning Skills – Revised (ABLLS-R). The following motor functions were analyzed: involuntary response to environmental changes; maintaining balance and control over own body within the center of gravity; the child’s ability to move from one place to another; object manipulation; the child’s hand skills; visual-motor coordination – to evaluate the child’s ability to use visual-perceptual skills to perform complex eye-hand coordination tasks such as grasping objects, building with blocks, copying pictures. Conclusion. Given the behavior patterns and sensory problems in the development of children with autism spectrum disorders, it can be reasonably argued that it is not only a specially organized process of formation of their motor sphere that is necessary but also the need to select special methods and techniques. Thus, considering the existing developments in the field of applied behavioral analysis, such teaching methods may include: NET (training in the natural environment), chain learning, functional communication training, discrete and mixed trials, etc. All these methods require special techniques that could be combined, for example, providing support for the error-free formation of motor skills and using a motivational environment. These directions seem promising for further research.